The effects of the economic crisis in the defense procurement - Fonfría, Antonio; Martín, Fernando (Papeles de Europa, 2017)
Procurement in the field of defense has a special importance because it is one of the ministries with the largest volume of expenditure and investment. The effects of the economic crisis, in its early years, were especially noticeable through significant budget reductions, which led to changes in procurement policies particularly in its technological orientation. This article analyzes more than 3,000 contracts in 2008 and 2011, showing the aspects in which the main changes in this area have been focused.
Keywords: Procurement; defense; Spain; economic crisis